(3YgOI GdEeGe jMji Hf MeRI Hf Ydi GdYdhi Edi HYV bVGJgs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3hef de jMce HeG CfRd Gddg aChdFc ge GdcGaQhf s
(3BNQgG (B:s
(3hYdi cGaI GdENhGf ef GdYdeGA hGdeJYdejf hSGFQ Cgd GdOjf hcGaI GdeSdejf hQMeg Gddg hHQcGfg hJMjGJg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B15s
(3GdfSNI HgG MhGTs
(3hcdGe ddeDda Edi HYV bVGg YUQgs
(3hLhGH GdeDda dQLd ef GdTGe cJH Edjg jSCdg Yf CMhGdg heUfaGJg heG bQC ef GdcJH heG gh Ydjg ef GdfGS s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds